Doc Hay: A Chinese Herbalist Combating the 1918-1919 Influenza Pandemic in America - Yemeng Chen (Wolters Kluwer Health/LWW, 2020)
This is a story about a Chinese herbalist Ing "Doc" Hay who combated the 1918-1919 influenza pandemic in the America West. As an immigrant, he came to the States as a laborer, but he had knowledge of Chinese herbal medicine due to his family heritage. This made it possible for him to start practicing in the Chinese community in John Day, Oregon, until 1948 when he retired. During the time of the pandemic running wild in the 1910s, he prescribed formulas aimed at flu and boiled herbal decoction, personally delivering it to a working site for those Chinese laborers as well as non-Chinese patients. None of the laborer patients treated by him died during this deadly pandemic. Due to his success and fame, his practice was booming even after the Chinese community disappeared in John Day in later years. Doc Hay is always remembered in the history of earlier development in eastern Oregon, so that the site of his practicing, Kam Wah Chung and Co. Building, is now a national historic landmark. And more importantly, he has also been remembered by Chinese herbal medicine practitioners in the United States.